Firm Capability dalam Teori Resource-Based View - Fransisca Mulyono (Jurnal Administrasi Bisnis, 2013)
The superior performance of the company sometimes is not determined by the exter-nal environment, but internal factors. This is the essence of the theory of resource -based view (RBV) which form the basis of this paper.According to the RBV theory, superior performance will be achieved when com-pany is able to achieve competitive advantage. Competitive advantage has capabilityantecedent which reflect the ability to manage its resources. There are three typesof capabilities described in this paper, namely : (1) dynamic capability (which is acompany’s ability to integrate its resources in order to respond to new opportunitiesin the external environment), (2) technological capability ( which is the ability of thecompany to develop existing technologies into the new technology that allows thecompany’s products in accordance with the market wants) and (3) managerial capa-bility (which is the ability of the company to ensure the implementation of efficientmanagement that will bring innovation).Based on three capabilities described above, it was clear that not only internalfactors are the focus of the company, but also external factors.Keywords: superior performance, dynamic capability, technlogical capability,managerial capability.